2018
DOI: 10.1172/jci.insight.120750
|View full text |Cite
|
Sign up to set email alerts
|

Ruxolitinib inhibits cyclosporine-induced proliferation of cutaneous squamous cell carcinoma

Abstract: Organ transplant recipients (OTRs) on cyclosporine A (CSA) are prone to catastrophic cutaneous squamous cell carcinoma (SCC). Allograft-sparing, cancer-targeting systemic treatments are unavailable. We have shown increased risk for catastrophic SCC in OTRs via CSA-mediated induction of IL-22. Herein, we found that CSA drives SCC proliferation and tumor growth through IL-22 and JAK/STAT pathway induction. We in turn inhibited SCC growth with an FDA-approved JAK1/2 inhibitor, ruxolitinib. In human SCC cells, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Using ruxolitinib, an FDA-approved JAK1/2 inhibitor, in human CSCC cells and xenografts reduces proliferation and growth. This could be a feasible option for preventing CSCC in OTRs who face long-term immunosuppression [154].…”
Section: Cyclosporine and Csccmentioning
confidence: 99%
“…Using ruxolitinib, an FDA-approved JAK1/2 inhibitor, in human CSCC cells and xenografts reduces proliferation and growth. This could be a feasible option for preventing CSCC in OTRs who face long-term immunosuppression [154].…”
Section: Cyclosporine and Csccmentioning
confidence: 99%
“…C-MYC-dependent pro-apoptotic protein NOXA upregulation confers inhibitor susceptibility for rapid BAK-dependent death. [68]T1, T8, MET1, MET4Early stage T1 demonstrates the greatest proliferative response to IL-22 treatment. cSCC proliferation was inhibited by JAK1/2 inhibitor ruxolitinib in vitro with tumour size reduction in vivo; however, this was demonstrated in the A431 cSCC epidermoid carcinoma line only and not in T1, T8, MET1 or MET4 lines.…”
Section: Table A1mentioning
confidence: 99%
“…An increased occurrence of non‐melanoma skin cancer (NMSC), such as cutaneous squamous cell carcinoma (cSCC), has not only been described following the long‐term treatment with the anti‐metabolite hydroxyurea (HU) but also under Janus kinase 1 and 2 inhibitors (JAKi) therapy for haematological malignancies. It has been reported that NMSC developing in patients on ruxolitinib therapy exhibit a more aggressive and metastatic profile 1–6 . We report a polycythaemia vera (PV) and long‐term HU and ruxolitinib therapy who developed highly aggressive cSCC not responding to cetuximab and pembrolizumab treatment.…”
Section: Introductionmentioning
confidence: 93%